PEMAHAMAN ASPEK METAFORA MUSIK LESUNG DALAM GENDHING KUPU TARUNG DI MAGETAN - Dea Lunny Primamona (Institut Seni Indonesia Surakarta, 2020)
The uniqueness of the rhytm pattern (gendhing) of the mortar in Magetan lies on the title of the gendhing-gendhing adopted from the name and behavior of the animal. This study focuses on the analysis of metaphorical aspects in the gendhing entitled Kupu Tarung. In this study, metaphor serves as a bridge that communicates certain messages contained in the gendhing Kupu Tarung. One of the results of this analysis is the name of gendhing Kupu Tarung originating from the moment of a mating butterfly, which is then captured in the image scheme, and represented by the creative power (fantasia power) of the community. The collision between the two types of butterfly genitals, which are the essence of the butterfly mating moment, is interpreted in the form of a link between pestles facing each other. Through this mortar gendhing, ancestors transmit the value of fertility (in terms of agriculture and also sexuality) to agrarian communities in the language of art.